THE ROLE OF RADIO FREE EUROPE IN THE IRON CURTAIN COUNTRIES: 1956 POZNAN UPRISING AND 1956 HUNGARIAN UPRISING - Aydemir, Emrah (My University, 2018)
The Cold War expanded with the East-West conflict and led to the battle of the greatpowers. The Soviet Union believed that communism would achieve a victory all around theworld and that Western imperialist powers had been historically hostile towards them, and thatthe Soviet Union was the leading Socialist/Communist state. Thus, the Soviet Union continuedto increase its influence and expansionist policies on the Iron Curtain countries. The Americans,on the other hand, tried to intend for the proper tools to reach the communist world under theleadership of the Soviet Union. A global disagreement emerged in the third world countries andideological conflicts of two superpowers was experienced in the world. In the conflicts, therewas no real military intervention between the United States and the Soviet Union. Instead ofthis, there had been a struggle of proxy wars conducted over third world countries. Radio wasone of the preferences of the United States of America in this struggle. To this end, the RadioFree Europe was designed and used by the United States of America for achieving the politicalgoals on the Iron Curtain countries. Radio Free Europe was used as a weapon against theSoviet Union in order to prevent the Soviet Union from establishing its political dominationthrough communist governments in the Iron Curtain countries. Radio Free Europe, whichcaused historical events in the Iron Curtain countries, met the information and news demand ofthe region. In this study, the role of Radio Free Europe in the Iron Curtain countries will beaddressed and its effects on the 1956 Pozna? Uprising and the 1956 Hungarian Uprising will beexamined.
Keywords: Tarih; Uluslararası İlişkiler